THE INFLUENCE OF LEADERSHIP STYLE AND ORGANIZATIONAL CULTURE ON EMPLOYEE PERFORMANCE THROUGH JOB SATISFACTION AS AN INTERVENING VARIABLE IN MEDAN CITY TRANSPORTATION SERVICE - Rini Astuti; Azizah Harahap (CERED Indonesia Institute, 2025)
The research conducted by the author aims to determine and analyze the influence of leadership style, organizational culture and satisfaction on employee performance, to determine and analyze the influence of leadership style and organizational culture on employee performance through job satisfaction, to determine and analyze the influence of leadership style on employee performance through job satisfaction and to determine and analyze the influence of organizational culture on employee performance through job satisfaction at the Medan City Transportation Agency. The population in this study was the Medan City Transportation Agency totaling 220 people with a sample of 69 people. Data collection techniques used in this study were Questionnaires (Questionnaire) and Interviews and Documentation. The analysis technique in the study used SmartPLS (Partial Least Square) starting from the measurement model (outer model), model structure (inner model) and hypothesis testing. The results of the study indicate that leadership style, organizational culture and job satisfaction influence employee performance, leadership style and organizational culture influence job satisfaction, leadership style influences employee performance through job satisfaction and organizational culture influences employee performance through job satisfaction at the Medan City Transportation Agency.